Radiation-Induced Malignancies of the Head and Neck: A Single-Center Population Study and Survival Outcomes. - Fraccaroli, Francesca; Giannini, Lorenzo; Cristofaro, Valentina; Alliata, Andrea; Cavalieri, Stefano; Deganello, Alberto (Current Oncology, 2026)
Simple Summary: Radiation therapy has significantly improved survival in patients with head and neck cancer. However, owing to the increased overall survival achieved with current treatments, a subset of patients may develop a new tumor within the previously irradiated area. These radiation-induced cancers are uncommon but very aggressive. They are more difficult to diagnose early because radiation causes tissue changes such as scarring and swelling that can hide the new cancer on imaging and physical examination. Treatment is also challenging, as tissues previously exposed to radiation are more fragile, and surgery may be harder to perform. In this study, we analyzed patients treated at a major cancer institute in Milan who developed a secondary cancer many years after radiotherapy. We examined tumor characteristics, treatments, and outcomes. Our findings show that surgery remains the most effective option when feasible, resulting in better survival. These results support the importance of lifelong follow-up after radiotherapy. Background: Radiation-induced malignancies (RIMs) of the head and neck are rare but serious long-term complications of radiotherapy. With increasing cancer survival rates, their incidence is rising. This study reports the clinicopathological features, treatment approaches, and survival outcomes of patients with head and neck RIMs managed at the National Cancer Institute (Istituto Nazionale dei Tumori—INT) in Milan, Italy. Methods: A retrospective analysis was conducted on patients diagnosed with head and neck RIMs between 2003 and 2024 at the Istituto Nazionale dei Tumori, Milan. Inclusion criteria comprised tumor development within the irradiated field, histological distinction from the primary neoplasm, latency exceeding three years, and absence of alternative etiologic factors. Clinical data were obtained from institutional records. Overall survival (OS) was estimated using the Kaplan–Meier method, with significance set at p < 0.05. Results: Fifty patients fulfilled the inclusion criteria (52% male; median age at primary diagnosis, 40 years). The mean latency between primary and secondary tumors was 20.8 years. The most frequent RIM site was the oral cavity, with squamous cell carcinoma as the predominant histology (66%). Surgery was performed in 66% of cases, achieving R0 resection in 67%. The 2- and 5-year OS rates were 67.4% and 39.3%, respectively, with significantly superior survival after surgery. Conclusions: Head and neck RIMs present substantial diagnostic and therapeutic challenges. Radical surgery remains the most effective treatment, while long-term surveillance and multicenter research are essential to optimize management and mitigate secondary tumor risk.